Spatial heterogeneity and Immune infiltration of cellular lysosomal pathways reveals a new blueprint for tumor heterogeneity in esophageal cancer - Wei, Jinxing; Wu, XiaoMing; Wang, Shuohao; Liu, Siqing; Gao, Xia (Frontiers in Endocrinology, 2023)
Background: Esophageal squamous cell carcinoma (ESCC) is a common GI malignancy with poor chemotherapeutic sensitivity and a low five-year survival rate. The potential association of the lysosomal pathway with ESCC has been initially investigated, but there is a lack of reported mechanisms linking the lysosomal pathway to immune infiltration and invasive metastasis in ESCC. METHODS: The cell type annotation of ESCC patients and the distribution of their gene markers were analysed by single cell data. They were also grouped according to the expression of lysosomal pathways. GSVA enriched pathway scoring, Cellchat cell communication was performed to demonstrate the tumour-associated pathway scores and interactions of different cell populations. In order to construct prognostic risk markers, related differential genes were screened. In order to determine the correlation between immune infiltration and tumor therapeutic drug sensitivity, lysosomal pathway-related gene risk scores were assessed by algorithms. In cellular experiments, qPCR and flow cytometry were used to assess the role of the lysosomal pathway gene-MT1X on tumour cell development. RESULTS: ESCC single cell data were annotated into 7 Cluster clusters by t-sne downscaling analysis. Cellchat analysis revealed that the "MIF" cellular communication network is the main communication mode of the lysosomal pathway in ESCC cells. The lysosomal pathway genetic risk model was found to be significantly different from ESCC prognosis in both the training and validation groups, and highly influenced the immune infiltration and chemotherapy sensitivity of ESCC patients. Cellular assays showed that the lysosomal pathway gene MT1X was less expressed in oesophageal cancer cells than in normal oesophageal epithelial cells. Knockdown of MT1X significantly promoted the growth rate of oesophageal cancer cells. Conclusion: Based on the single cell sequencing technology and transcriptomic analysis, we confirmed that there is a close association between the lysosomal pathway and the immune infiltration and immune pathway of ESCC, and the constructed lysosomal pathway risk score is closely associated with the treatment sensitivity and growth reproduction of ESCC. This suggests that the interaction between the lysosomal pathway and immune infiltration may be a potential target for new directions in ESCC treatment.